Fraught intimacies: toward the impossibility of women's kinship. Issue 1 (2nd January 2023) - Delsandro, Erica Gene; Mitchell, Jennifer
ABSTRACT: This essay argues that recognizing and examining the fraught intimacies among modernist women writers and among the female characters they create is necessary for feminist modernist scholars. The two modernist authors at the center of this essay, Nella Larsen and Jean Rhys, write relationships among women that illustrate the way white heteronormative patriarchy constrains and ultimately denies the cultivation of a mutually sustaining intimacy between women. Delsandro and Mitchell conclude their reading by acknowledging that feminist modernist studies has focused more on recuperation and revision rather than the difficult conversations attendant upon the acknowledgement that not all of the women writers feminist scholars have recovered have succeeded in their feminism.